The importance of adopting International Public Sector Accounting Standards (IPSAS) in improving public sector governance in Algeria. - arioua, Mohad; tahiri, Sofiane (Journal of Research in Finance and Accounting, 2025)
This study aimed highlight the contribution of International Public Sector Accounting Standards (IPSAS) to improving public sector governance in Algerian upon the adoption and implementation of these Standards, first the international public Sector Accounting Standards adopted in Algerian were discussed, followed by an examination of public sector governance, and then a review of how the adoption International Accounting Standards affectively contributes to improving Public Sector governance.